Распространение возмущений в акустической ферромагнитной среде - Селезов, И.Т. (Доповіді НАН України, 2019)
Приведено обобщение уравнений распространения волновых возмущений в акустической ферромагнитной
среде с конечной скоростью, как развитие исследований в области акустики. В отличие от традиционных
уравнений феррогидродинамики обобщенные уравнения учитывают конечность скорости распространения
волн, что влияет на разогрев широко применяемых феррогерметизаторов, особенно в начальной стадии. Приведено узагальнення рівнянь поширення хвильових збурень в акустичному феромагнітному середовищі зі скінченною швидкістю, як розвиток досліджень в області акустики. На відміну від традиційної
моделі ферогідродинаміки узагальнені рівняння враховують скінченність швидкості поширення хвиль,
що впливає на розігрівання широко застосованих ферогерметизаторів, особливо на початковій стадії. A generalization of the equations for the propagation of wave perturbations in the acoustic ferromagnetic medium
with a finite speed are presented, as a development of researches in the region of acoustics. Unlike the
traditional equations of ferrohydrodynamics, the generalized equations involve the finiteness of a speed of propagating
waves, that influences the warming-up of widely used ferrohermetics, especially in the initial stage. The
developed generalized equations include, as particular cases, the known continual equations taking the effect
of a magnetic field into account. These equations can be useful in applications.